Abundance of Ordo Lepidoptera in The Land Conversion of Ciwidey Pine Forest - Mulyono, Sabella Friska S.; Suhara, Suhara; Kurniawan, Iwan Setia (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
The study entitled